A Comprehensive Review of Experimental Rodent Models of Repeated Blast TBI - Skotak, Maciej; Townsend, Molly T.; Ramarao, Kakulavarapu V.; Chandra, Namas (Frontiers in Neurology, 2019)
We reviewed the relevant literature delineating advances in the development of the experimental models of repeated blast TBI (rbTBI). It appears this subject is a relatively unexplored area considering the first work published in 2007 and the bulk of peer-reviewed papers was published post-2011. There are merely 34 papers published to date utilizing rodent rbTBI models. We performed a meta-analysis and extracted basic parameters to capture the characteristics of the exposure conditions (the blast intensity, inter-exposure interval and the number of exposures), the age and weight of the animal models most commonly used in the studies, and their endpoints. Our analysis revealed three strains of rodents are predominantly used: Sprague Dawley and Long Evans rats and wild type (C57BL/6J) mice, and young adult animals 8 to 12-week-old are a preferred choice. Typical exposure conditions are the following: 1) peak overpressure in the 27-145 kPa (4-21 psi) range, 2) number of exposures: 2 (13.9%), 3 (63.9%), 5 (16.7%) or 12 (5.6%) with a single exposure used for a baseline comparison in 41.24% of the studies. Two inter-exposure interval durations were used: 1) short (1-30 min.) and 2) extended (24 hours) between consecutive shock wave exposures. The experiments included characterization of repeated blast exposure effects on auditory, ocular and neurological function, with a focus on brain etiology in most of the published work. We present an overview of major histopathological findings, which are supplemented by studies implementing MRI (DTI) and behavioral changes after rbTBI in the acute (1 to 7 days post-injury), subacute (7 to 14 days) and chronic (> 14 days) phases post-injury.